Notes on Lipschitz estimates for the stop and play operator in plasticity - Lang, Holger; Dressler, Klaus; Pinnau, René; Speckert, Michael (Applied Mathematics Letters, 2009)
We present a generalisation of existing Lipschitz estimates for the stop and play operator for an arbitrary convex and closed characteristic, which contains the origin, in a separable Hilbert space. We are especially concerned with the dependence of stop and play on different scalar products. © 2008 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.ltd.noteso
Keywords: Absolutely continuous functions; Convex sets; Elasticity; Hysteresis; Plasticity; Rate independence; Variational inequalities